Fructosamine or glycated haemoglobin as a measure of diabetic control? - Allgrove, J (1988)
Glycated haemoglobin A1 (HbA1c), fructosamine, and total serum proteins were measured in 30 normal and 61 diabetic children. The normal range for HbA1c was 4.7-8.8% and for fructosamine was 0.98-1.88 mmol/l. These were similar to adult normal ranges and there were no significant age differences during childhood. There was a highly significant correlation between HbA1c and fructosamine in the diabetic children but this was lost when only concentrations within the established normal ranges were considered. Adjustment of concentrations of fructosamine for total serum proteins made no difference to the results. Changes in HbA1c and fructosamine were followed in three newly diagnosed patients and in one whose diabetes was getting worse. HbA1c decayed with a half life of 28.7 days and fructosamine decayed with a half life of 16.5 days. Fructosamine concentrations were lower than expected in the patients who were improving and higher than expected in the patient who was deteriorating. It is suggested that while fructosamine is not a direct substitute for HbA1c it may be a useful adjunct in determining whether a patient is worsening or improving in the short term. A change from HbA1c to fructosamine for routine assessment of diabetes while retaining HbA1c on selected occasions would result in some cost savings while retaining the advantages of having both assays available.